CLINICAL DIFFICULTIES IN ENDODONTIC TREATMENT OF PREMOLARS WITH ATYPICAL ANATOMY - Aleksandra Pecheva; Kostadin Georgiev (Peytchinski Publishing, 2022)
To achieve high levels of success in endodontic treatment requires in-depth knowledge of the anatomy and morphology of the root canal system. Premolars are a group of teeth which shows a wide spectrum of different variations, reaching the apical opening. The frequency of one root canal at the apical tip for the maxillary first premolars is 8.66%, while 89.64% of the examined teeth show two root canals at the apical tip. The frequency of two or more root canals in the mandibular first premolars varies between 2.7% to 62.5%, while the frequency of two or more root canals in the mandibular second premolars varies between 0% and 34.3%. Some of the clinical aspects in the treatment of such aberrated premolars include implementing detailed preoperative evaluation- X-Rays and CBCT, sufficient opening of the endodontic access and careful three-dimentional cleaning of the root canal system with combination of different endodontic instruments and hybrid techniques of work and following hermetic sealing of all portals of exits. A 3D printing after a CBCT scan is a method of choice when a clinician wants to master the anatomy of a premolar. Knowledge of the complex root canal system is essential for understanding the principles and problems of shaping and, cleaning, determining the apical boundaries and dimensions of the root canals.